Latent Profiles of Early Language Development in a Large Finnish-Speaking Sample of the FinnBrain Birth Cohort Study - Saloranta, Essi; Yada, Akie; Mccauley, Stewart; Yli-Savola, Aura; Savo, Satu; Renvall, Kati; Eskola, Eeva; Fernandes, Michelle; Korja, Riikka; Karlsson, Hasse; Karlsson, Linnea; Mainela-Arnold, Elina (American Speech Language Hearing Association, 2026)
Purpose: Research on early language development has primarily used two categories to group at-risk children, differing by the age at which risk is identified. Late talkers are toddlers with late onset of language development, some of whom may catch up with peers. Developmental language disorder is used to refer to children above the age of 4 years. To this day, the longitudinal relationship between the two categories remains unclear. In this study, we explored early language trajectories in a large birth cohort using exploratory methodology to gain better understanding of the types and prevalence of language trajectories from 14 months to 5 years of age, with particular interest in risk trajectories that cluster statistically.
Method: We conducted latent profile analysis (LPA) on seven language variables collected between 1 and 5 years of age (N = 1,281). Multinomial logistic regression procedure was used to identify child and family characteristics that predicted profile memberships.
Results: The LPA yielded three profiles of language development described as persistent low, stable average, and stable high. Female sex, longer duration of pregnancy, and higher maternal socioeconomic status increased the odds of belonging to the stable high-language profile, whereas male sex and not being first born increased the odds of belonging to persistent low language profile.
Conclusions: Contrary to previous research, we did not observe increasing or decreasing profiles, suggesting that toddler language difficulties tend to persist at age 5 years, at least in this birth cohort. This suggests commencing language intervention early instead of the wait-and-see approach.
Supplemental material: https://doi.org/10.23641/asha.29441471.